Servant Leadership in Government Institution, is it Effective? - Imam Buchori; Justine Tanuwijaya; Andreas Wahyu Gunawan (Management Analysis Journal, 2023)
The aim of this studiy is to examine the effect of servant leadership on job performance directly and indirectly through the mediating effect of job involvement and job satisfaction. Data were collected through questionnaires by Google Froms and analyzed using Structural Equation Modeling (SEM) with AMOS24. A total of 174 civil servant at the one of Indonesian government agencies in audit services participated as research sample. The results of this study reveal that servant leadership has significant positive effect toward job involvement and job satisfaction, but it has a negative effect toward job performance. Furthermore, this study is expected to contribute to the organization to encourage the role of leaders for prioritizing the employees’ interests to increase job satisfaction and job involvement so that can improve employees’ performance, especially in the public sector.